Researching and writing based on multiple texts. (April 2020) - Du, Hongcui; List, Alexandra
Abstract: Students perform poorly on multiple text reading-writing (MTRW) tasks. To address this issue, we examine students' strategy engagement during response composition by analyzing five types of data. These include: (a) log data of text access, (b) the notes that students composed during processing, (c) students' modified think-aloud reports, (d) screen-capture videos of writing behaviors, and (e) the written products generated. We report on insights gained by coordinating and juxtaposing these various sources of data on students' writing. Results showed that while students accessed and took notes on the majority of the texts provided, information from texts was rarely connected, neither in students' notes nor in the written responses composed. Moreover, students' effortful engagement in multiple text use, captured via log data, was associated with task performance. Finally, a number of variables, corresponding to students' strategy reports during processing, were found to be significant predictors of writing performance. Highlights: Five data sources were examined to understand students' writing based on multiple texts. Students' information use was associated across log data of text access and written notes. Revision behaviors were limited and largely topographical in nature. Writing strategies reported via a cued think-aloud were associated with writing task performance.